Basolateral Amygdala Is Involved in Modulating Consolidation of Memory for Classical Fear Conditioning - Vazdarjanova, Almira (J Neurosci, 1999)
Previous findings indicate that the basolateral amygdala complex of nuclei (BLC) is involved in modulating (i.e., enhancing or impairing) memory consolidation for aversive training such as inhibitory avoidance. The present study examined whether the BLC also modulates the consolidation of memory for classical fear conditioning in which a specific context is paired with footshock. Adult male rats with bilateral cannulae targeting the BLC were allowed, first, to habituate in a Y maze that had differently shaped and textured arms. On the next day the rats were placed in one maze arm (shock arm), and they received four unsignaled footshocks. In Experiment 1, immediately after the training some rats received BLC inactivation with lidocaine (10 μg/0.2 μl per side), and control rats received buffered saline. In Experiment 2, rats received immediate post-training intra-BLC infusions of the muscarinic receptor agonist oxotremorine (10 ng/0.2 μl per side) or saline. On a 24 hr retention test each rat was placed in a “safe” arm of the maze and allowed to access all maze arms. Lidocaine-treated rats had impaired memory for the classical fear conditioning when they were compared with the saline-treated controls: they spent less time freezing, entered the shock arm more readily and more often, and spent more time in it. In contrast, oxotremorine-treated rats had a stronger memory for the context–footshock association as assessed by all measures of memory. Thus, post-training treatments affecting BLC function modulate memory for Pavlovian contextual fear conditioning in a manner similar to that found with other types of training.